PENINGKATAN KETERBUKAAN DIRI (Self-Disclosure) DENGAN TEKNIK PETAK JOHARI MELALUI BIMBINGAN KELOMPOK DI SMA NEGERI 2 DI KOTA BENGKULU KELAS X MIPA F - anik febrianti (Psikodidaktika, 2018)
Openness Self(Self-Disclosure) is the attitude of the individual able and willing to provide information about himself personally, and open and willing to accept the opinions of others to trust someone to be a friend to share. This study aims to: 1) Knowing how the level of the Self Disclosure students at SMAN 2 Bengkulu city F Class X Mathematics and Natural Sciences before being awarded with Technical Guidance Services Group Plots Johari. 2) Knowing how the level of the Self Disclosure students at SMAN 2 Bengkulu city F Class X Mathematics and Natural Sciences after being awarded with Technical Guidance Services Group Plots Johari. 3) Knowing the success of the group with technical guidance services Johari plots in increasing Disclosure Self-student at SMAN 2 Bengkulu city F Class X Mathematics and Natural Sciences. The method used in the research was a class act. The subjects were students of class XI SMA N 2 F MIPA Bengkulu City. The procedure of classroom action research conducted through four (4) stages: 1) planning, 2) implementation, 3) observation, 4) Reflection. Once the data is collected and analyzed obtained the following results: (1) At each cycle of increased openness Yourself students, On Pre Test of 30 students there are eight students who have low levels of self openness as much as 5 students with a percentage of 62.5% and the level of openness Being self as much as 3 students with a percentage of 37.5%. (2) In the first cycle, the level of openness of students improve their self becomes Self Disclosure levels were as much as 6 students with a percentage of 75% and a high level of self Disclosure much as 2 people with a percentage of 25%. In the third cycle, the degree of openness of the Self increases to moderate as much as 1 students with a percentage of 12.5% and higher by 7 students with a percentage of 87.5%. (3) Implementation Guidance Services group with Johari plot technique can increase the level of self Disclosure students at SMAN 2 Bengkulu city F Class X Mathematics and Natural Sciences .